Promotional effects of Me (Sb, La, Ce, Mo) additives on the NH3-SCR activity and SO2 durability of V2O5-WO3/TiO2 catalysts - Jung, Min Gie; Shin, Jung Hun; Kwon, Dong Wook; Hong, Sung Chang (Institution of Chemical Engineers, 2024)
In this study, we investigated the effects of incorporating Sb, La, Ce, and Mo additives into V2O5-WO3/TiO2 catalysts with high vanadium content for NH3-SCR. The addition of Sb, La, or Ce to the V-site of the V4/W5/G5 catalyst led to improved reaction activity, which was attributed to an increase in the nonstoichiometric V4+(3+) ratio and enhanced surface adsorbed oxygen species. Fast-SCR due to NO2 oxidation resulted in increased the reaction rates. Conversely, Mo addition reduced reaction rates. Durability against SO2 improved after incorporating Sb, La, Ce, or Mo, which was attributed to SO2 adsorption inhibition by Sb and Mo, and SO2 consumption by La and Ce forming sulfate species. Sb, Ce, and Mo additives facilitated ABS (ammonium bisulfate, (NH4)HSO4) decomposition at lower temperatures compared to the V4/W5/G5 catalyst, with distinctive NH3 and SO2 desorption profiles. Particularly, Mo addition induced NH3 desorption from ABS decomposition at a low temperature of 177 °C.